Influence of Choline Chloride on the Phase Equilibria and Partition Performance of Polymer/Polymer Aqueous Biphasic Systems - Alves, Mariana B. N.; Lopes, André M.; Santos, Nathalia A. [UNESP]; Santos-Ebinuma, Valéria C. [UNESP]; Vicente, Filipa A.; Pereira, Jorge F. B. [UNESP] (MDPI, 2023)
A series of polymeric aqueous biphasic systems (ABS) were determined using polyethylene glycol (PEG) and sodium polyacrylate (NaPA) with choline chloride ([Ch]Cl) as an adjuvant. The effect of (i) PEG and NaPA molecular weights, (ii) PEG functionalization, (iii) [Ch]Cl addition (at different concentrations), and (iv) temperature (25, 37 and 50 °C) was evaluated through their ability to promote the two-phase separation. The results showed that the polymerization degree and functionalization of PEG polymers exhibit a large influence on the ABS formation, with high molecular weight PEG inducing an increase in the biphasic region. Furthermore, the addition of small amount (1–5 wt%) of [Ch]Cl also increased the liquid–liquid demixing. Temperature and the increase in the NaPA molecular weight did not influence the ABS formation ability. Finally, the partition performance of PEG/NaPA + [Ch]Cl ABS was evaluated using caffeine as a model compound. Unlike the ABS formation trend, NaPAs molecular weight significantly influenced the partitioning, which was strengthened when using NaPA-8000. Moreover, the incorporation of [Ch]Cl facilitated an inversion in the partitioning behavior of caffeine, thereby emphasizing the remarkable partitioning tailoring potential exhibited by these systems. Overall, all systems seem to be promising alternatives for the effective extraction, purification and/or concentration of different value-added biomolecules.
Keywords: aqueous two-phase systems; caffeine; choline chloride; polyethylene glycol; sodium polyacrylate